ALDH1A3 Regulations of Matricellular Proteins Promote Vascular Smooth Muscle Cell Proliferation - Xie, Xiujie; Urabe, Go; Marcho, Lynn; Stratton, Matthew; Guo, Lian-Wang; Kent, Craig K. (iScience, 2019)
Vascular smooth muscle cell (VSMC) proliferation promotes intimal hyperplasia (IH) in occluding vascular diseases. Here we identified a positive role of ALDH1A3 (an aldehyde dehydrogenase) in this pro-IH process. The expression of ALDH1A3, but not that of 18 other isoforms of the ALDH family, was substantially increased in cytokine-stimulated VSMCs. PDGF(BB) stimulated VSMC total ALDH activity and proliferation, whereas ALDH1A3 silencing abolished this effect. ALDH1A3 silencing also diminished the expression of two matricellular proteins (TNC1 and ESM1), revealing a previously unrecognized ALDH1A3 function. Loss-of-function experiments demonstrated that TNC1 and ESM1 mediated ALDH1A3's pro-proliferative function via activation of AKT/mTOR and/or MEK/ERK pathways. Furthermore, ALDH inhibition with disulfiram blocked VSMC proliferation/migration in vitro and decreased TNC1 and ESM1 and IH in angioplasty-injured rat carotid arteries. Thus, ALDH1A3 promotes VSMC proliferation at least partially through TNC1/ESM1 upregulation; dampening excessive ALDH1A3 activity represents a potential approach to IH mitigation. [Display omitted] •The ALDH1A3 isoform promotes vascular smooth muscle cell proliferation•ALDH1A3's function is mediated by its upregulation of TNC1 and ESM1•The pan-ALDH inhibitor drug disulfiram mitigates intimal hyperplasia Pathophysiology; Vascular Remodeling; Molecular Biology; Molecular Mechanism of Behavior